TINGKAT PENGETAHUAN MASYARAKAT MENGENAI EPILEPSI DI LINGKUNGAN X KELURAHAN TEGAL SARI MANDALA II MEDAN - YUNI VALENTRI LUMBAN TOBING; NURCAHAYA SINAGA (JURNAL ILMIAH SIMANTEK, 2021)
Epilepsy is one of the most common serious a chronic neurological disorder that is present all over the world. Based on thereport of WHO (World Health Organization) more than 50 million people worldwide have epilepsy. Low-level knowledge ofthe disease causes people with epilepsy to be discriminated and stigmatized. This research aims to know The level ofsociety knowledge about epilepsy in X Neighborhood, Tegal Sari Mandala II Village, Medan. This methode use a descriptivestudy with cross sectional design. The populations in this research are all community members in X Neighborhood, TegalSari Mandala II Village, Medan and 91 samples were taken with consecutive sampling technique. The results of the researchshowed that of the 91 respondents, female respondents (70,3%) are more than men (29,7%), The majority of respondentsages ranged from 26-45 years (56,0%), The majority of respondents worked as a self-employed (39,6%). 72,5% of themfinished elementary or junior high school. Majority of respondents have enough knowledge about epilepsy (46,2%). The levelof society knowledge about epilepsy in X Neighborhood, Tegal Sari Mandala II Village, Medan had enough.